Development of cross-linking strategies for DNA G-quadruplexes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University, Manawatu, New Zealand - Chilton, Bruce (Massey University, 2019)
Chemically modified DNA structures are an important development in the study of DNA properties. They allow the manipulation of biophysical properties of DNA complexes, which can give unique perspectives on the behaviours of DNA and molecules, such as enzymes, which interact with DNA. The use of chemical modification to study G-quadruplex structures has been limited, but has shown potential as a method of controlling their topology and behaviour. We plan to achieve this by functionalising positions within quadruplex forming sequences and using this to create linkages between strands. We predict this will improve the stability of the secondary structure and improve kon, the association rate, of the complex. We discuss several general approaches to G-quadruplex modification, and further discuss specific strategies for carrying out these modifications. One general method for modifying DNA is directly modifying the nucleotides that make up the sequence. G-quadruplexes are primarily composed of guanosine, modification of which is primarily possible at two positions, 2 and 8, due to the hydrogen bond arrangement within the structure. We target the 2- and 8- position of modified guanosine molecules with amine substitutions and Sonogashira coupling processes, respectively. We report the synthesis of sequences containing thiol functionalised nucleotides, and an initial assessment of their biophysical properties. The second general method for modifying DNA is incorporating unique, non-native nucleotides with specific functionalities. This has previously been accomplished by incorporating ligands directly into sequences, which were used to form G-quadruplexes with transition metal ions such as copper(II), nickel(II) and cobalt(II). We aim to synthesise sequences containing a modified sugar and incorporate pyridine instead of a nucleobase. We hope this will provide quadruplexes which more closely mimic the structure of native complexes, improving the previously observed properties of modified G-quadruplexes formed in the presence of transition metal ions. We present the synthesis and biophysical properties of a unique quadruplex forming sequence containing a 4-pyridine ligand and pyrrolidine sugar. The thermal stability and kinetic properties of these modified structures are examined using circular dichroism spectroscopy, demonstrating the change in properties relative to native G4 DNA.
Keywords: Quadruplex nucleic acids; Synthesis; DNA; Synthesis